2016
DOI: 10.1038/npp.2016.24
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Labeling of Parvalbumin Neurons and Perineuronal Nets in the Dorsolateral Prefrontal Cortex of Subjects with Schizophrenia

Abstract: Alterations in cortical parvalbumin (PV)-containing neurons, including a reduced density of detectable neurons and lower PV levels, have frequently been reported in the dorsolateral prefrontal cortex (DLPFC) of schizophrenia subjects. Most PV neurons are surrounded by perineuronal nets (PNNs) and the density of PNNs, as detected by Wisteria floribunda agglutinin (WFA) labeling, has been reported to be lower in schizophrenia. However, the nature of these PNN alterations, and their relationship to disease-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
146
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(168 citation statements)
references
References 53 publications
(71 reference statements)
20
146
1
1
Order By: Relevance
“…This hypothesis is based on findings that experimental manipulations in model systems which reduce glutamatergic drive to PV interneurons result in lower PV interneuron activity accompanied by lower expression of activity-dependent gene products (e.g., PV and the GABA-synthesizing enzyme glutamic acid decarboxylase 67, GAD67), abnormal gamma oscillations and working memory deficits(9-12). Consistent with this hypothesis, postmortem studies have repeatedly shown lower PV and GAD67 levels in the DLPFC of schizophrenia subjects(13-17), which are thought to reflect lower glutamatergic drive to a subset of PV neurons and not a loss of PV neurons in the illness(13, 15, 18, 19). These deficits do not seem to be due to a global reduction in excitatory drive to all interneuron subtypes, as calretinin-containing (CR) interneurons, the most abundant interneuron subtype in the primate DLPFC(20), appear to be relatively unaffected in schizophrenia(15, 16, 21).…”
Section: Introductionmentioning
confidence: 85%
“…This hypothesis is based on findings that experimental manipulations in model systems which reduce glutamatergic drive to PV interneurons result in lower PV interneuron activity accompanied by lower expression of activity-dependent gene products (e.g., PV and the GABA-synthesizing enzyme glutamic acid decarboxylase 67, GAD67), abnormal gamma oscillations and working memory deficits(9-12). Consistent with this hypothesis, postmortem studies have repeatedly shown lower PV and GAD67 levels in the DLPFC of schizophrenia subjects(13-17), which are thought to reflect lower glutamatergic drive to a subset of PV neurons and not a loss of PV neurons in the illness(13, 15, 18, 19). These deficits do not seem to be due to a global reduction in excitatory drive to all interneuron subtypes, as calretinin-containing (CR) interneurons, the most abundant interneuron subtype in the primate DLPFC(20), appear to be relatively unaffected in schizophrenia(15, 16, 21).…”
Section: Introductionmentioning
confidence: 85%
“…Deterioration of PNN may manifest as changes in intensity without a loss of PNN+ cell density (Enwright et al, 2016). To determine PNN intensity throughout A1 and at the single cell level, images were converted into 8-bit format (where 0 is total absence of PNN).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the decreased activity of pyramidal cells is thought to reduce excitation of parvalbumin basket (PVb) cells through various activity-dependent mechanisms involving GAD67, PV, Zif268, and PNNs. 216219 Furthermore, dysregulated splicing of ERBB4 and lower expression of dysbindin may contribute to compromised excitatory drive to PVb cells. 220222 Additional changes to GABA interneurons include deficits in PV chandelier cells (PVCh), SST, and CCK cells.…”
Section: Figurementioning
confidence: 99%